(untitled) (SCAFFOLD: A SHOWCASE OF VANDERBILT FIRST-YEAR WRITING, 2021)
Health disparities operate on a social stratification system and manifests itself on a socioeconomic status “ladder”. These systems function so that White people, no matter where they are on the SES ladder, typically have better health outcomes than their Black and Hispanic counterparts. Because of this trend, I hypothesized: If this is the case across racial lines, would it still be the case amongst members of the same racial group? This specific disparity is a subset of racism; instead, it is called colorism -prejudice or discrimination against individuals with a dark skin tone, typically among people of the same ethnic or racial group. Colorism functions similarly to racism in that they both thrive upon institutional, white-supremacist systems in our society; however, colorism is a form of racism that is most commonly practiced by victims of societal racism themselves. For additional context, listen to the author’s reflection on this piece below.